HUBUNGAN ANTARA KADAR GULA REDUKSI, JUMLAH SEL MIKROB DAN ETANOL DALAM PRODUKSI BIOETANOL DARI FERMENTASI AIR KELAPA DENGAN PENAMBAHAN UREA - Putri, Santi Andriani; Restuhadi, Fajar '; ', Rahmayuni ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This research was conducted to determine the best concentration of urea in bioethanol fermentation from coconut water using Saccharomyces cerevisiae in increasing ethanol production. This research was done experimentally using four treatments and two replications. The combination of urea levels were U1 (without urea), U2 (0,2 g/l), U3 (0,4 g/l) and U4 (0,6 g/l). Observations were made every 24 hours for 3 days include ethanol production, sugar reduction and the number of cells microbes. Data obtained from the analysis descriptively using tabulation and graphs. The best treatment was found in U3 (urea 0,4 g/l) with the highest ethanol’s yield of 11,25%, reduction of residual sugar amount of 168,13 g/l and the number of cells/mL of 1,0x109 in the three day. Keywords: bioethanol, coconut water, urea, fermentation